Strengthening The Creative Economy Through Entrepreneurship Efforts To Improve Cirebon Community - Salwa Anjani (Business Finence Analyst Co.,, 2024)
In facing business competition, the empowerment of human resources needs to be optimized so that people can be competitive, independent and able to compete with other products on the market in the era of the industrial revolution 4.0. The era of revolution 4.0 is a challenge in itself for MSMEs so that efforts are made to overcome these problems, namely socialization of Entrepreneurship and product innovation, socialization of Digital Marketing, socialization of Digital Payment, and investment counseling. The debriefing process requires the role of Community Service Program so that the goals can be created, namely the welfare of the community and educating businessman in business development in the future. This is expected that businessman will be able to create product improvement steps, and several aspects that need to be considered in running a business so that businessman in the Mangunharjo RW 03 will be more independent and innovative in facing business competition in the era of the industrial revolution 4.0.